2015
DOI: 10.1021/ie5042484
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Hydrodechlorination of Chloromethanes with Activated-Carbon-Supported Metallic Catalysts

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(97 reference statements)
1
3
0
Order By: Relevance
“…A similar behavior follow Rh/CM and Ru/CM when DCM is used as the reactant, however the selectivity to chlorinated products considerably increases for the HDC of TCM with these catalysts, specially for Ru/CM. This is in agreement with kinetics results obtained with similar catalyst [35]. In a previous work where a kinetic study of the HDC of DCM and TCM to obtain methane with carbon supported Pd, Pt, Rh and Ru catalysts was performed it was found that Pd/C and Pt/C followed a LHHW model controlled by adsorption.…”
Section: Catalytic Activitysupporting
confidence: 91%
“…A similar behavior follow Rh/CM and Ru/CM when DCM is used as the reactant, however the selectivity to chlorinated products considerably increases for the HDC of TCM with these catalysts, specially for Ru/CM. This is in agreement with kinetics results obtained with similar catalyst [35]. In a previous work where a kinetic study of the HDC of DCM and TCM to obtain methane with carbon supported Pd, Pt, Rh and Ru catalysts was performed it was found that Pd/C and Pt/C followed a LHHW model controlled by adsorption.…”
Section: Catalytic Activitysupporting
confidence: 91%
“…In In the literature, the HDC technology has been used for the removal of the chlorinated pollutant or the production of valuable products from chlorinated compounds. Complete conversion and almost complete dechlorination have been achieved for DCM [1,18,20,21,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], TCM [1,18,20,21,23,27,[31][32][33][34]43,[47][48][49][50] and TTCM [27,. Additionally, the upgrading of residual chloromethanes for the production of valuable hydrocarbons, such as light olefins or paraffins, which could be used as feedstock in chemical and petrochemical industries, has also been explored in recent years [32][33][34]48].…”
Section: Synthesis Of Catalysts For Hydrodechlorination Active Phase ...mentioning
confidence: 99%
“…For the two different studies, the common experiments' conditions are: operation at atmospheric pressure; employing a total flow rate of 100 N cm 3 min −1 ; a reagents molar ratio of 100 (H 2 /DCM); a reaction temperature of 250 • C. The inlet DCM concentration for both studies was 1000 ppmv, which was prepared by mixing a DCM/N 2 commercial mixture and N 2 in the appropriate ratios (both gases supplied by Praxair, Madrid, Spain). According to a previous study, under these conditions, transfer limitations might be discarded [39]. The catalysts were reduced in situ under continuous H 2 flow at 300 • C for 90 minutes prior to the HDC experiments.…”
Section: Catalytic Activity Experimentsmentioning
confidence: 99%